Mechanisms of immunogenicity in colorectal cancer. Issue 10 (19th June 2019) - Sillo, T O; Beggs, A D; Morton, D G; Middleton, G
Abstract: Background: The immune response in cancer is increasingly understood to be important in determining clinical outcomes, including responses to cancer therapies. New insights into the mechanisms underpinning the immune microenvironment in colorectal cancer are helping to develop the role of immunotherapy and suggest targeted approaches to the management of colorectal cancer at all disease stages. Method: A literature search was performed in PubMed, MEDLINE and Cochrane Library databases to identify relevant articles. This narrative review discusses the current understanding of the contributors to immunogenicity in colorectal cancer and potential applications for targeted therapies. Results: Responsiveness to immunotherapy in colorectal cancer is non-uniform. Several factors, both germline and tumour-related, are potential determinants of immunogenicity in colorectal cancer. Current approaches target tumours with high immunogenicity driven by mutations in DNA mismatch repair genes. Recent work suggests a role for therapies that boost the immune response in tumours with low immunogenicity. Conclusion: With the development of promising therapies to boost the innate immune response, there is significant potential for the expansion of the role of immunotherapy as an adjuvant to surgical treatment in colorectal cancer. Graphical Abstract: This narrative review highlights current understanding of the mechanisms of immunogenicity in colorectal cancer. The roles of germline, somatic and epigenetic factors in determining the immune environment in colorectal cancer are considered, and the significant potential for targeted immune therapies to improve patient outcomes is discussed. Role for the future